Fuzzy-based Closed-loop Speed Control of Induction Motor Fed from Matrix Converter - Erdem, Ebubekir; Tatar, Yetkin; Sunter, Sedat (Taylor & Francis Inc, 2011)
In this study; closed-loop speed control of an induction motor that was achieved by a fuzzy-based slip regulation technique has been performed. As a power source for the motor, a three-phase matrix converter has been used, and the space-vector modulation was adapted for the generation of the switching control signals. Real-time control signals for the matrix converter were generated through MATLAB/Simulink (The MathWorks, Natick, Massachusetts, USA) supported digital signal processor control card. The space-vector modulation technique used in this work is simpler than other control algorithms, both in terms of implementation and the input power factor control. Furthermore, the proposed space-vector modulation technique for the matrix converter reduced turn-on number of the switching devices in a switching period, and therefore, fewer switching losses have occurred. Simulation and corresponding experimental results were given for various operating conditions.
Keywords: matrix converter; space vector modulation; fuzzy logic controller